Non-pharmaceutical interventions for containment, mitigation and suppression of COVID-19 infection (2020)
ABSTRACT: Background: The best scientific evidence is required to design effective Non-pharmaceutical interventions to help policymakers to contain COVID-19. Aim: To describe which Non-pharmaceutical interventions used different countries and a when they use them. It also explores how Non-pharmaceutical interventions impact the number of cases, the mortality, and the capacity of health systems. Methods: We consulted eight web pages of transnational organizations, 17 of international media, 99 of government institutions in the 19 countries included, and besides, we included nine studies (out of 34 identified) that met inclusion criteria. Result: Some countries are focused on establishing travel restrictions, isolation of identified cases, and high-risk people. Others have a combination of mandatory quarantine and other drastic social distancing measures. The timing to implement the interventions varied from the first fifteen days after detecting the first case to more than 30 days. The effectiveness of isolated non-pharmaceutical interventions may be limited, but combined interventions have shown to be effective in reducing the transmissibility of the disease, the collapse of health care services, and mortality. When the number of new cases has been controlled, it is necessary to maintain social distancing measures, self-isolation, and contact tracing for several months. The policy decision-making in this time should be aimed to optimize the opportunities of saving lives, reducing the collapse of health services, and minimizing the economic and social impact over the general population, but principally over the most vulnerable. The timing of implementing and lifting interventions could have a substantial effect on those objectives. Keywords: COVID-19; Coronavirus; Health Impact Assessment; Public Health; Quarantine; Review.